Penerapan senam anti-hipertensi terhadap perubahan tekanan darah sebagai strategi pencegahan hipertensi emergensi - Rycco Darmareja; Mar'atul Isnainyah; Nabila Tsamara Zahra; Clarissa Carera (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2026)
One of the emergency complications that usually occurs is hypertension. Physical exercise, such as Anti-Hypertension Exercises, is one of the efforts needed to control blood pressure and reduce the risk of complications. This program aims to improve community understanding and skills in controlling blood pressure through activity training (anti-hypertension exercises) to prevent hypertension-related emergencies. A health education method that provided education, demonstration, and practice of Anti-Hypertension Exercises together was carried out with 48 people with hypertension in the Kebagusan area, Pasar Minggu, Jakarta. The results of the activity showed an increase in public knowledge and attitudes about preventing hypertension emergencies through Anti-Hypertension Exercises and changes in blood pressure, both systolic, diastolic, and MAP, before and after the activity. It is hoped that Anti-Hypertension Exercises activities can be carried out consistently so that blood pressure can be controlled and reduce the risk of complications of hypertension emergencies.